Time, space, stars & man : The story of the Big Bang - Woolfson, Michael M. (Imperial College Press, 2013)
This book traces the causal pathway from the Big Bang through matter formation, stars and planets, life on Earth and the evolution of humans, presenting cosmology, particle physics, planetary science and evolution in an accessible narrative form.